Sei sulla pagina 1di 16

http://rahmahsamuri-rahms.blogspot.

com

ONE-SCHOOL.NET
Add Maths Formulae List: Form 4 (Update 18/9/08)

01 Functions

Absolute Value Function Inverse Function

If y = f ( x ) , then f −1 ( y ) = x
f ( x ), if f ( x ) ≥ 0
f ( x) Remember:
− f ( x), if f ( x ) < 0 Object = the value of x
Image = the value of y or f(x)
f(x) map onto itself means f(x) = x

02 Quadratic Equations

General Form Quadratic Formula

ax 2 + bx + c = 0
−b ± b 2 − 4ac
where a, b, and c are constants and a ≠ 0. x=
2a
*Note that the highest power of an unknown of a
quadratic equation is 2. When the equation can not be factorized.

Forming Quadratic Equation From its Roots: Nature of Roots

If α and β are the roots of a quadratic equation


b c
α +β =− αβ = b 2 − 4ac >0 ⇔ two real and different roots
a a
b 2 − 4ac =0 ⇔ two real and equal roots
The Quadratic Equation b 2 − 4ac <0 ⇔ no real roots
x 2 − (α + β ) x + αβ = 0 b 2 − 4ac ≥0 ⇔ the roots are real
or
x − ( SoR ) x + ( PoR ) = 0
2

SoR = Sum of Roots


PoR = Product of Roots

http://www.one-school.net/notes.html 1
http://rahmahsamuri-rahms.blogspot.com

ONE-SCHOOL.NET
03 Quadratic Functions

General Form Completing the square:

f ( x) = ax 2 + bx + c f ( x) = a ( x + p)2 + q

where a, b, and c are constants and a ≠ 0. (i) the value of x, x = − p


(ii) min./max. value = q
*Note that the highest power of an unknown of a (iii) min./max. point = (− p, q)
quadratic function is 2. (iv) equation of axis of symmetry, x = − p

Alternative method:
a > 0 ⇒ minimum ⇒ ∪ (smiling face)
f ( x) = ax 2 + bx + c
a < 0 ⇒ maximum ⇒ ∩ (sad face)
b
(i) the value of x, x = −
2a
b
(ii) min./max. value = f (− )
2a
b
(iii) equation of axis of symmetry, x = −
2a

Quadratic Inequalities Nature of Roots

a > 0 and f ( x) > 0 a > 0 and f ( x) < 0


b 2 − 4ac > 0 ⇔ intersects two different points
at x-axis
a b a b b − 4ac = 0 ⇔ touch one point at x-axis
2

b 2 − 4ac < 0 ⇔ does not meet x-axis

x < a or x > b a< x<b

04 Simultaneous Equations

To find the intersection point ⇒ solves simultaneous equation.

Remember: substitute linear equation into non- linear equation.

http://www.one-school.net/notes.html 2
http://rahmahsamuri-rahms.blogspot.com

ONE-SCHOOL.NET
05 Indices and Logarithm

Fundamental if Indices Laws of Indices

Zero Index, a0 = 1 a m × a n = a m+n


1
Negative Index, a −1 =
a a m ÷ a n = a m−n
a
( ) −1 =
b ( a m ) n = a m× n
b a

1 ( ab) n = a n b n
Fractional Index an = a n

m a n an
an = a n m
( ) = n
b b
Fundamental of Logarithm Law of Logarithm

log a y = x ⇔ a x = y log a mn = log a m + log a n

log a a = 1 log a
m
= log a m − log a n
n
log a a x = x
log a mn = n log a m
log a 1 = 0
Changing the Base

log c b
log a b =
log c a

1
log a b =
logb a

http://www.one-school.net/notes.html 3
http://rahmahsamuri-rahms.blogspot.com

ONE-SCHOOL.NET
06 Coordinate Geometry

Distance and Gradient


Distance Between Point A and C =
(x1 − x2 )2 + (x1 − x2 )2

y2 − y1
Gradient of line AC, m =
x2 − x1
Or
⎛ y − int ercept ⎞
Gradient of a line, m = − ⎜ ⎟
⎝ x − int ercept ⎠

Parallel Lines Perpendicular Lines

When 2 lines are parallel, When 2 lines are perpendicular to each other,

m1 = m2 . m1 × m2 = −1

m1 = gradient of line 1
m2 = gradient of line 2

Midpoint A point dividing a segment of a line

⎛ x1 + x2 y1 + y2 ⎞ A point dividing a segment of a line


Midpoint, M = ⎜ , ⎟ ⎛ nx + mx2 ny1 + my2 ⎞
⎝ 2 2 ⎠ P =⎜ 1 , ⎟
⎝ m+n m+n ⎠

http://www.one-school.net/notes.html 4
http://rahmahsamuri-rahms.blogspot.com

ONE-SCHOOL.NET
Area of triangle:

Area of Triangle

1
=
2

1
A=
2
( x1 y2 + x2 y3 + x3 y1 ) − ( x2 y1 + x3 y2 + x1 y3 )

Form of Equation of Straight Line


General form Gradient form Intercept form

ax + by + c = 0 y = mx + c x y
+ =1
a b
m = gradient
c = y-intercept b
a = x-intercept m=−
b = y-intercept a

Equation of Straight Line


Gradient (m) and 1 point (x1, y1) 2 points, (x1, y1) and (x2, y2) given x-intercept and y-intercept given
given
y − y1 = m( x − x1 ) y − y1 y2 − y1 x y
= + =1
x − x1 x2 − x1 a b

Equation of perpendicular bisector ⇒ gets midpoint and gradient of perpendicular line.

Information in a rhombus:
A B
(i) same length ⇒ AB = BC = CD = AD
(ii) parallel lines ⇒ mAB = mCD or mAD = mBC
(iii) diagonals (perpendicular) ⇒ mAC × mBD = −1
(iv) share same midpoint ⇒ midpoint AC = midpoint
D BD
C (v) any point ⇒ solve the simultaneous equations

http://www.one-school.net/notes.html 5
http://rahmahsamuri-rahms.blogspot.com

ONE-SCHOOL.NET
Remember:

y-intercept ⇒ x = 0
cut y-axis ⇒ x = 0
x-intercept ⇒ y = 0
cut x-axis ⇒ y = 0
**point lies on the line ⇒ satisfy the equation ⇒ substitute the value of x and of y of the point into the
equation.

Equation of Locus
( use the formula of The equation of the locus of a The equation of the locus of a moving
distance) moving point P ( x, y ) which is point P ( x, y ) which is always
The equation of the locus of a always at a constant distance equidistant from two fixed points A and B
moving point P ( x, y ) which from two fixed points is the perpendicular bisector of the
is always at a constant A ( x1 , y1 ) and B ( x2 , y 2 ) with straight line AB.
distance (r) from a fixed point a ratio m : n is
A ( x1 , y1 ) is PA = PB
PA m ( x − x1 ) + ( y − y1 ) 2 = ( x − x2 ) 2 + ( y − y2 ) 2
2
=
PA = r PB n
( x − x1 ) 2 + ( y − y1 ) 2 = r 2 ( x − x1 ) 2 + ( y − y1 ) 2 m 2
=
( x − x2 ) + ( y − y 2 ) 2 n 2

More Formulae and Equation List:

SPM Form 4 Physics - Formulae List


SPM Form 5 Physics - Formulae List

SPM Form 4 Chemistry - List of Chemical Reactions


SPM Form 5 Chemistry - List of Chemical Reactions

All at One-School.net

http://www.one-school.net/notes.html 6
http://rahmahsamuri-rahms.blogspot.com

ONE-SCHOOL.NET
07 Statistics
Measure of Central Tendency

Grouped Data
Ungrouped Data
Without Class Interval With Class Interval
Mean
Σx Σ fx Σ fx
x= x= x=
N Σf Σf

x = mean x = mean x = mean


Σx = sum of x Σx = sum of x f = frequency
x = value of the data f = frequency x = class mark
N = total number of the x = value of the data
data (lower limit+upper limit)
=
2
Median
m = TN +1 m = TN +1 ⎛ 1N −F⎞
2 2 m = L + ⎜⎜ 2 ⎟⎟ C
When N is an odd number. When N is an odd number. ⎝ fm ⎠

m = median
TN + TN TN + T N L = Lower boundary of median class
+1 +1
m= 2 2
m= 2 2 N = Number of data
2 2 F = Total frequency before median class
When N is an even When N is an even number. fm = Total frequency in median class
number. c = Size class
= (Upper boundary – lower boundary)

Measure of Dispersion

Grouped Data
Ungrouped Data
Without Class Interval With Class Interval

variance
σ =2∑ x2
−x
2
σ =2∑ fx 2
−x
2
σ =
2 ∑ fx 2
−x
2

N ∑f ∑f
σ = variance σ = variance σ = variance

Σ(x − x )
2
Σ(x − x )
2
Standard Σ f (x − x)
2
σ= σ=
Deviation N N σ=
Σf
Σx 2 Σx 2
σ= − x2 σ= − x2 Σ fx 2
N N σ= − x2
Σf

http://www.one-school.net/notes.html 7
http://rahmahsamuri-rahms.blogspot.com

ONE-SCHOOL.NET

The variance is a measure of the mean for the square of the deviations from the mean.

The standard deviation refers to the square root for the variance.

Effects of data changes on Measures of Central Tendency and Measures of dispersion

Data are changed uniformly with


+k −k ×k ÷k
Measures of Mean, median, mode +k −k ×k ÷k
Central Tendency
Range , Interquartile Range No changes ×k ÷k
Measures of
Standard Deviation No changes ×k ÷k
dispersion
Variance No changes × k2 ÷ k2

08 Circular Measures
Terminology

Convert degree to radian:


Convert radian to degree:
π
D xo = ( x × )radians
180 180
×
π 180
x radians = ( x × ) degrees
π
radians degrees

π
×
180D

Remember:

180D = π rad 1.2 rad


O
??? 0.7 rad ???
360 = 2π rad
D

http://www.one-school.net/notes.html 8
http://rahmahsamuri-rahms.blogspot.com

ONE-SCHOOL.NET
Length and Area

r = radius
A = area
s = arc length
θ = angle
l = length of chord

Arc Length: Length of chord: Area of Sector: Area of Triangle: Area of Segment:

s = rθ θ 1 2 1 2 1 2
l = 2r sin A= rθ A= r sin θ A= r (θ − sin θ )
2 2 2 2

09 Differentiation

Differentiation of a Function I
Gradient of a tangent of a line (curve or
straight) y = xn
dy δy dy
= lim ( ) = nx n−1
dx δ x →0 δ x dx

Example
y = x3
Differentiation of Algebraic Function
dy
Differentiation of a Constant = 3x 2
dx
y=a a is a constant
dy
=0 Differentiation of a Function II
dx
y = ax
Example dy
y=2 = ax1−1 = ax 0 = a
dx
dy
=0
dx Example
y = 3x
dy
=3
dx

http://www.one-school.net/notes.html 9
http://rahmahsamuri-rahms.blogspot.com

ONE-SCHOOL.NET
Differentiation of a Function III Chain Rule

y = ax n y = un u and v are functions in x


dy dy dy du
= anx n−1 = ×
dx dx du dx

Example Example
y = 2 x3 y = (2 x 2 + 3)5
dy du
= 2(3) x 2 = 6 x 2 u = 2 x 2 + 3, therefore = 4x
dx dx
dy
y = u5 , therefore = 5u 4
du
Differentiation of a Fractional Function
dy dy du
= ×
1 dx du dx
y=
xn = 5u 4 × 4 x
Rewrite = 5(2 x 2 + 3) 4 × 4 x = 20 x(2 x 2 + 3) 4
y = x−n
dy −n Or differentiate directly
= − nx − n−1 = n+1 y = (ax + b) n
dx x
dy
= n.a.(ax + b) n −1
Example dx
1
y=
x y = (2 x 2 + 3)5
y = x −1 dy
= 5(2 x 2 + 3) 4 × 4 x = 20 x(2 x 2 + 3) 4
dy −1 dx
= −1x −2 = 2
dx x

Law of Differentiation

Sum and Difference Rule

y =u±v u and v are functions in x


dy du dv
= ±
dx dx dx

Example
y = 2 x3 + 5 x 2
dy
= 2(3) x 2 + 5(2) x = 6 x 2 + 10 x
dx

http://www.one-school.net/notes.html 10
http://rahmahsamuri-rahms.blogspot.com

ONE-SCHOOL.NET
Product Rule Quotient Rule

y = uv u and v are functions in x u


y= u and v are functions in x
dy du dv v
= v +u
dx dx dx du dv
v −u
dy dx dx
=
Example dx v2
y = (2 x + 3)(3 x 3 − 2 x 2 − x)
Example
u = 2x + 3 v = 3x3 − 2 x 2 − x
x2
du dv y=
=2 = 9 x2 − 4 x − 1 2x +1
dx dx
u = x2 v = 2x +1
dy du dv
=v +u du dv
dx dx dx = 2x =2
dx dx
=(3 x − 2 x − x)(2) + (2 x + 3)(9 x 2 − 4 x − 1)
3 2
du dv
v −u
dy
= dx 2 dx
Or differentiate directly dx v
y = (2 x + 3)(3x3 − 2 x 2 − x) dy (2 x + 1)(2 x) − x 2 (2)
=
dy dx (2 x + 1) 2
= (3x3 − 2 x 2 − x)(2) + (2 x + 3)(9 x 2 − 4 x − 1)
dx 4 x2 + 2 x − 2 x2 2 x2 + 2 x
= =
(2 x + 1) 2 (2 x + 1) 2

Or differentiate directly
x2
y=
2x +1
dy (2 x + 1)(2 x) − x 2 (2)
=
dx (2 x + 1) 2
4 x2 + 2 x − 2 x2 2 x2 + 2 x
= =
(2 x + 1) 2 (2 x + 1) 2

http://www.one-school.net/notes.html 11
http://rahmahsamuri-rahms.blogspot.com

ONE-SCHOOL.NET
Gradients of tangents, Equation of tangent and Normal

Gradient of tangent at A(x1, y1):

dy
= gradient of tangent
dx

Equation of tangent: y − y1 = m( x − x1 )

Gradient of normal at A(x1, y1):

1
mnormal = −
mtangent
If A(x1, y1) is a point on a line y = f(x), the gradient 1
of the line (for a straight line) or the gradient of the = gradient of normal
− dy
dy dx
tangent of the line (for a curve) is the value of
dx Equation of normal : y − y1 = m( x − x1 )
when x = x1.

Maximum and Minimum Point

dy
Turning point ⇒ =0
dx

At maximum point, At minimum point ,


2
dy d y dy d2y
=0 <0 =0 >0
dx dx 2 dx dx 2

http://www.one-school.net/notes.html 12
http://rahmahsamuri-rahms.blogspot.com

ONE-SCHOOL.NET
Rates of Change Small Changes and Approximation
Small Change:
dA dA dr
Chain rule = ×
dt dr dt δ y dy dy
≈ ⇒ δ y ≈ ×δ x
δ x dx dx
dx
If x changes at the rate of 5 cms -1 ⇒
=5 Approximation:
dt
Decreases/leaks/reduces ⇒ NEGATIVES values!!! ynew = yoriginal + δ y
dy
= yoriginal + ×δ x
dx

δ x = small changes in x
δ y = small changes in y
If x becomes smaller ⇒ δ x = NEGATIVE

http://www.one-school.net/notes.html 13
http://rahmahsamuri-rahms.blogspot.com

ONE-SCHOOL.NET
10 Solution of Triangle

Sine Rule: Cosine Rule: Area of triangle:


a
a b c a2 = b2 + c2 – 2bc cosA
= = b2 = a2 + c2 – 2ac cosB
sin A sin B sin C C
c2 = a2 + b2 – 2ab cosC
b
Use, when given
ƒ 2 sides and 1 non included b2 + c2 − a 2
cos A =
angle 2bc 1
ƒ 2 angles and 1 side A= a b sin C
2
Use, when given
ƒ 2 sides and 1 included angle C is the included angle of sides a
a a B ƒ 3 sides and b.
A
A a a c
b 180 – (A+B)
A
b b

http://www.one-school.net/notes.html 14
http://rahmahsamuri-rahms.blogspot.com

ONE-SCHOOL.NET

Case of AMBIGUITY If ∠C, the length AC and length AB remain unchanged,


the point B can also be at point B′ where ∠ABC = acute
A
and ∠A B′ C = obtuse.
If ∠ABC = θ, thus ∠AB′C = 180 – θ .
180 - θ
θ Remember : sinθ = sin (180° – θ)
C B′ B
Case 1: When a < b sin A Case 2: When a = b sin A
CB is too short to reach the side opposite to C. CB just touch the side opposite to C

Outcome: Outcome:
No solution 1 solution
Case 3: When a > b sin A but a < b. Case 4: When a > b sin A and a > b.
CB cuts the side opposite to C at 2 points CB cuts the side opposite to C at 1 points

Outcome: Outcome:
2 solution 1 solution

Useful information:
In a right angled triangle, you may use the following to solve the
c problems.
b (i) Phythagoras Theorem: c = a 2 + b2
θ
a Trigonometry ratio:
(ii)
sin θ = bc , cos θ = ac , tan θ = b
a

(iii) Area = ½ (base)(height)

http://www.one-school.net/notes.html 15
http://rahmahsamuri-rahms.blogspot.com

ONE-SCHOOL.NET
11 Index Number
Price Index Composite index

P1 Σ Wi I i
I = × 100 I=
P0 Σ Wi

I = Price index / Index number I = Composite Index


P0 = Price at the base time W = Weightage
P1 = Price at a specific time
I = Price index

I A, B × I B ,C = I A,C ×100

http://www.one-school.net/notes.html 16